Assessing the Effectiveness of EU Countries in Implementing the Paris Agreement - Frank Best; Anita Tang (ZBW - Leibniz Information Centre for Economics, 2024)
Climate change, a transnational issue, necessitates international collaboration for effective mitigation. Despite the progress achieved by the Paris Agreement of 2015, a significant milestone in global cooperation, its implementation remains a challenge for both the international community and individual countries. Because of the agreement's optional nature, there are significant differences in terms of the ambition and achievement levels among signatories. The European Union (EU) stands out because of its unique structure and common policies, yet there is a lack of empirical research into their impact on climate policy effectiveness. This paper aims to fill this gap by comparing the effectiveness of the implementation between EU and non-EU countries in terms of policy output, achieving climate targets and an economically sustainable transition. Quantitative regression models show no significant differences concerning policy output and the achievement of climate targets, while they demonstrate greater ambition and success in economically sustainable transition. Our findings contribute to a better understanding of effective climate policies, highlight the positive impact of EU leadership in this regard, and stress the importance of international cooperation. – – Der Klimawandel, ein transnationales Thema, erfordert internationale Zusammenarbeit für eine effektive Minderung. Trotz des Fortschritts, der durch das Pariser Abkommen von 2015 erreicht wurde, ein bedeutender Meilenstein in der globalen Zusammenarbeit, bleibt dessen Umsetzung sowohl für die internationale Gemeinschaft als auch für die einzelnen Länder eine Herausforderung. Aufgrund der freiwilligen Natur des Abkommens gibt es erhebliche Unterschiede hinsichtlich des Ambitionsniveaus und der Zielerreichung unter den Unterzeichnerstaaten. Die Europäische Union (EU) sticht aufgrund ihrer einzigartigen Struktur und gemeinsamen Politiken hervor, doch es mangelt an empirischer Forschung zu deren Auswirkungen auf die Wirksamkeit der Klimapolitik. Diese Arbeit zielt darauf ab, diese Lücke zu schließen, indem die Wirksamkeit der Umsetzung zwischen EU- und Nicht-EU-Ländern im Hinblick auf politische Ergebnisse, das Erreichen von Klimazielen und einen wirtschaftlich nachhaltigen Übergang verglichen wird. Quantitative Regressionsmodelle zeigen keine signifikanten Unterschiede in Bezug auf politische Ergebnisse und das Erreichen von Klimazielen, weisen jedoch auf eine größere Ambition und einen größeren Erfolg beim wirtschaftlich nachhaltigen Übergang hin. Unsere Ergebnisse tragen zu einem besseren Verständnis effektiver Klimapolitiken bei, unterstreichen die positive Rolle der EU-Führung in diesem Bereich und betonen die Bedeutung internationaler Zusammenarbeit.
Keywords: C12; E65; F53; H11; Q58; Q54; 330; climate change; climate policy; Ambition; Climate Policy Effectiveness; climate targets; sustainable transition; Effectiveness; EU Climate Policy; EU Policy; Paris Agreement; Paris Agreement; Paris Agreement Implementation; policy output